2019
DOI: 10.1007/s13592-019-00641-8
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee rebel workers preferentially respond to high concentrations of sucrose

Abstract: The honeybee is one of several eusocial species with a complex set of anatomical, physiological, and behavioural traits that are correlated with foraging preferences. Sensory sensitivity to sucrose is associated with the foraging preferences of workers, with individuals that are less sensitive to sugar preferring to forage for nectar and those that are highly sensitive to sucrose preferring to forage for pollen. In this study, we test this hypothesis by comparing the sucrose responsiveness of genetically simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Thus, workers developing at larval stage in a queenless colony become relatively selfish individuals with higher reproductive potential than those that develop in a colony with a queen. These workers called rebel workers are characterized not only by their increased reproductive potential but also other altered anatomical features (e.g., less developed HGs, larger mandibular glands; [ 20 ]), shortened preimaginal development [ 22 ], prolonged life [ 23 ], different foraging preferences [ 24 ], tendency to drift to other colonies [ 25 ], increased sucrose sensitivity [ 26 ], energy reserves and protein concentrations in fat body [ 4 ], and increased learning ability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, workers developing at larval stage in a queenless colony become relatively selfish individuals with higher reproductive potential than those that develop in a colony with a queen. These workers called rebel workers are characterized not only by their increased reproductive potential but also other altered anatomical features (e.g., less developed HGs, larger mandibular glands; [ 20 ]), shortened preimaginal development [ 22 ], prolonged life [ 23 ], different foraging preferences [ 24 ], tendency to drift to other colonies [ 25 ], increased sucrose sensitivity [ 26 ], energy reserves and protein concentrations in fat body [ 4 ], and increased learning ability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that there is no trade-off between these two biological functions in honeybee workers. Previous studies showed that rebel workers were less sensitive than normal workers to the sucrose concentration in solutions and did not respond to a solution with a low sugar concentration (Karolina Kuszewska et al 2019). The difference in sucrose sensitivity between these two groups of workers can influence the speed of learning.…”
Section: Discussionmentioning
confidence: 99%
“…However, we think that OA does not have much of an impact on the results of our study for two reasons. First, rebel workers, which learned faster, are less sensitive to sugar concentration than normal workers, which learned slower (Kuszewska et al 2019). Second, in our study, we used 21day-old bees, all of which were foragers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their ovaries are activated regardless of whether they live in queen-less or queen-right colonies [ 14 , 15 , 16 , 17 , 18 ]. Moreover, rebels typically have prolonged life [ 16 ], different foraging preferences [ 18 ], tendency to drift to other colonies [ 17 ], increased sucrose sensitivity [ 19 ], increased energy reserves and protein concentrations in the fat body [ 20 ], and increased learning ability [ 21 ]. We posited that rebels are not only similar to queens in some anatomical, morphological and behavioral features, but also develop in a shorter time in comparison to normal workers, i.e., they might undergo shorter ontogeny.…”
Section: Introductionmentioning
confidence: 99%